Cognitive Reserve in Dementia: Implications for Cognitive Training - Mondini, Sara; Madella, Ileana; Zangrossi, Andrea; Bigolin, Angela; Tomasi, Claudia; Michieletto, Marta; Villani, Daniele; Di Giovanni, Giuseppina; Mapelli, Daniela (Frontiers in Aging Neuroscience, 2016)
Cognitive reserve (CR) is a potential mechanism to cope with brain damage. The aim of this study was to evaluate the effect of cognitive reserve on a cognitive training (CT) in a group of patients with dementia. 86 participants with mild to moderate dementia were identified by their level of CR quantified by the Cognitive Reserve Index questionnaire (CRIq) and underwent a cycle of CT. A global measure of cognition (MMSE) was obtained before (T0) and after (T1) the training. Multiple linear regression analyses highlighted CR as a significant factor able to predict changes in cognitive performance after the CT. In particular, patients with lower CR benefited from a CT program more than those with high CR. These data show that CR can modulate the outcome of a CT program and that it should be considered as a predictive factor of neuropsychological rehabilitation training efficacy in people with dementia.